Benin : 2010 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility; Staff Report; Staff Supplements and Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Benin. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The goal of the last ECF arrangement (2005-09) was to support Benin's strategy to achieve higher sustainable growth and reduce poverty while preserving macroeconomic stability and reducing vulnerabilities to external shocks. The program achieved most of its objectives. The main macroeconomic challenge ahead is to mitigate the impact of the crisis in the short term, while reaching higher sustainable growth over the medium term. The government's economic program is geared properly to pursue these objectives. The structural reform agenda is appropriately ambitious.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet